ANALYSIS OF TEACHER QUALITIES FOR SUCCESSFUL HISTORY LESSONS IN GENERAL AND TECHNICAL HUMANITIES CYCLES IN KINDU - KANDOLO MUSINGILWA Thomas (IJRDO - Journal of Social Science and Humanities Research, 2026)
This study falls within the framework of the didactics of history teaching. When discussing history education, several factors can influence student learning. These include the students’ own skills, expectations, motivation, and behavior, as well as parental education. However, teachers’ qualifications, knowledge, attitudes, and practices, along with the school climate, are also crucial to the learning process. Didactics of teaching addresses the conditions under which knowledge, skills, and attitudes are acquired. In the case of history teaching, its success depends on the collaboration of several stakeholders, such as the physical and pedagogical organization of schools, the teachers (who are the focus of this research), the students, the parents, and even the overall school environment. Currently, we have thought it important to reflect on the teaching of History in the general and technical humanities of Kindu by emphasizing the qualities that can be attributed to the teacher so that he succeeds in his lessons in this discipline.